Alat Pendidikan Islam Dalam Perspektif Kontemporer: Analisis Literatur Dan Implikasinya - Darmawan, Tri Yudha; Nasution, M. Abdul Qoyyum Bey; Ihsan, M. Fadhilah (Journal of Sustainable Education, 2025)
This study aims to analyze various tools of Islamic education from a contemporary perspective and to examine their implications for the learning process and character development of students. In the modern era, marked by technological advancement and rapid socio-cultural changes, Islamic education is required to adapt while maintaining its fundamental values. The method used in this research is library research with a qualitative-descriptive approach. Data were obtained through analysis of classical and contemporary literature, including scientific journals, reference books on Islamic education, and relevant research findings. The results of the study indicate that Islamic educational tools are not limited to conventional media such as books and blackboards, but also include digital media, social environments, teacher role models, and the integration of spiritual values into learning technology. The implications of these findings highlight the importance of developing Islamic educational strategies that are contextual, innovative, and grounded in the principles of monotheism (tawhid), ethics (akhlaq), and transcendental awareness. This study is expected to contribute to the development of Islamic educational practices that are more relevant to contemporary needs.